Improving CH4 production and energy conversion from CO2 and H2 feedstock gases with mixed methanogenic community over Fe nanoparticles. (October 2020) - Cheng, Jun; Dong, Haiquan; Zhang, Haihua; Yuan, Luyun; Li, Hui; Yue, Liangchen; Hua, Junjie; Zhou, Junhu
Highlights: CH4 yield from CO2 and H2 feedstock gases was enhanced with Fe nanoparticles. Methanothermobacter abundance markedly increased from 7 to 16%. Conversion efficiency of CO2 to CH4 increased from 52.9 to 92.9%. Electrochemical characteristics of anaerobic sludge were improved. Abstract: To achieve methanogenic community optimization and improve the conversion efficiency of CO2 to CH4, Fe nanoparticles were used to promote the Methanothermobacter abundance in methanogens, which significantly increased the conversion efficiency of CO2 and H2 feedstock gases to CH4 product. High-throughput 16S rRNA gene sequencing analysis revealed that Methanothermobacter abundance markedly increased from 7 to 16% when the Fe nanoparticles concentration increased from 0 to 1.5 g/LR (the working volume in the bioreactor). Therefore, the CH4 yield significantly promoted from 0.105 to 0.186 L/LR . However, when the Fe nanoparticles concentration was further increased to 2 g/LR, methanogenesis was inhibited due to toxic effects. The electron transfer constant kapp of anaerobic sludge increased by 32.8-fold to 5.77 × 10 −2 s −1 when the Fe nanoparticles concentration increased from 0 to 1.5 g/LR, which significantly promoted carbon conversion efficiency from 52.9 to 92.9% and energy conversion efficiency from 46.3 to 76.9%.